Electromagnetic properties of Li0.4Fe2.4Zn0.2O4 ferrite sintered by continuous electron beam heating - Malyshev A. V. Andrei Vladimirovich; Nikolaeva S. A. Svetlana Andreevna; Lysenko E. N. Elena Nikolaevna; Vlasov V. A. Vitaliy Anatolievich (2016, 2016)
Title screen